2017
DOI: 10.5858/arpa.2017-0040-ra
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Role for Programmed Death Ligand-1 Testing and Immunotherapy in Colorectal Cancer With Microsatellite Instability? Part I—Colorectal Cancer: Microsatellite Instability, Testing, and Clinical Implications

Abstract: - Although the TNM classification of malignant tumor stage remains the key determinant of CRC prognosis and treatment, there are considerable stage-independent, interindividual differences in clinical outcome and therapy response by patients. In addition, MSI-H status has an important role in CRC management and can be reliably detected by molecular and immunohistochemistry techniques and genetic testing. Efforts must be made to identify whether MSI-H CRC is germline or sporadic to ensure appropriate treatment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 47 publications
0
41
0
Order By: Relevance
“…Dendritic cells present TAAs to helper CD4 + T cells via the MHC-2 pathway. Helper T cells secrete interferon α, interleukins, and other substances to improve the sensitivity of tumours to toxic T cells [4]. Therefore, we also investigated the prognostic value of CD4 expression.…”
Section: Subgroup Analysis Of the Prognostic Value Of Cd8 Expression mentioning
confidence: 99%
See 1 more Smart Citation
“…Dendritic cells present TAAs to helper CD4 + T cells via the MHC-2 pathway. Helper T cells secrete interferon α, interleukins, and other substances to improve the sensitivity of tumours to toxic T cells [4]. Therefore, we also investigated the prognostic value of CD4 expression.…”
Section: Subgroup Analysis Of the Prognostic Value Of Cd8 Expression mentioning
confidence: 99%
“…Tumours can express antigens, known as tumour-associated antigens (TAAs), which trigger immune responses [11,12]. Patients with dMMR present higher levels of TAAs and increased TILs than patients with proficient MMR (pMMR) [4,13]. Many studies have shown that TIL density is closely related to tumour prognosis [14,15].…”
mentioning
confidence: 99%
“…The Cancer Genome Atlas classi cation [2] and Consensus Molecular subtype classi cation [3] both de ne a subgroup of patients with de cient mismatch repair (dMMR) and show microsatellite instability high (MSI-H). MSI is the molecular ngerprint of dMMR [4]. Pathological features for dMMR CRC are typically associated with poor differentiation and increased tumour-in ltrating lymphocytes (TILs) [4].…”
Section: Introductionmentioning
confidence: 99%
“…MSI is the molecular ngerprint of dMMR [4]. Pathological features for dMMR CRC are typically associated with poor differentiation and increased tumour-in ltrating lymphocytes (TILs) [4]. The National Comprehensive Cancer Network guidelines [5] state that patients with stage II MSI-H have a better prognosis and do not bene t from uorouracil adjuvant therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation